PERTUMBUHAN DAN HASIL GANYONG (Canna Edulis Ker.) PADA BEBERAPA TINGKAT NAUNGAN DAN TAKARAN PUPUK KANDANG - Sri Muhartini (Universitas Sebelas Maret, 2009)
This research is executed on month of April until with November 2004 on the house agricultural Conducting Majors wirings UGM’s agricultural Faculties. There is aim even this research it to get naungan’s zoom and den manure measuring that nicest for ganyong’s growth and result.Design that is utilized is Split Plots 3x3 one be arranged in Slot Design is divided. Its main slot (main plots) are level consisting of naungan 3 (three) border which is N0=naungan 0% (without naungan), N25=naungan 25% and N50=naungan 50%. Its slot child (plotted sub) are measuring manure consisting of den 3 (three) border which is P0,5=10 tons/ha; P1,0=20 tons/ha and P1,5=30 tons/ha.Observed variable high cover plant, total leaf, total anakan, plants fresh weight, far ranging leaf, rimpang’s weight, rimpang’s diameter, long rimpang, rimpang’s colour, rimpang’s spreading character.Equired data of yielding observational analyzed with variant of analysis on trusty ladder 95% and if available reality difference among conduct therefore drawned out by Duncan New’s quiz’s Multiple Range Test (DMRT) on bias ladder 5%.Of research result can be concluded that 1) naungan 50% constitute nicest naungan zoom for ganyong’s vegetative growth, 2) naungan 25% constitute nicest naungan zoom for rimpang’s result (weight, long and rimpang’s diameter), 3) measuring manure den 30 tons/ha constitutes den mnaure measuring that nicest for ganyong’s growth and result, and 4) production sharing the best one combine rimpang on naungan’s conduct 25% and den manure as big as 300 tons/ha (1,5 kg/plants).